High-toughness heat-conducting polylactic acid composite material and preparation method thereof

By using nanofillers such as bacterial cellulose, graphene nanosheets and carbon nanotubes in polylactic acid composite materials, combined with aqueous phase predispersion and melt blending in situ crosslinking technology, a thermal conductivity functional network is built, which solves the problem of the reduction of tensile strength of existing materials when improving thermal conductivity and impact toughness, and achieves the comprehensive performance of high strength and tough thermal conductivity.

CN119592027APending Publication Date: 2025-03-11HUBEI KEPUDA OPTIC-ELECTRIC MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411468304.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When existing polylactic acid composites improve thermal conductivity and impact toughness, they usually lead to a decrease in tensile strength, making it difficult to achieve high tensile strength, impact strength and thermal conductivity at the same time.

Method used

Nanofillers such as bacterial cellulose, graphene nanosheets and carbon nanotubes are used, combined with aqueous phase predispersion and melt blending in situ crosslinking technology to build a thermal conductivity network to enhance the thermal conductivity, strength and toughness of the material.

Benefits of technology

The high tensile strength (up to 55MPa), high impact strength (up to 10kJ/m2) and high thermal conductivity (up to 7w/m2·K) of polylactic acid composites are achieved, while maintaining good processing performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-toughness heat-conducting polylactic acid composite material and a preparation method thereof, and belongs to the technical field of composite materials. The composite material is prepared from the following raw materials in parts by weight: 50-80 parts of polylactic resin, 5-20 parts of bacterial cellulose, 5-20 parts of heat-conducting filler, 5-10 parts of polyethylene glycol, 1-5 parts of a reducing agent, 1-5 parts of a cross-linking agent, 0.2-2 parts of an antioxidant and 0.2-2 parts of a lubricant. The preparation method comprises the following steps: preparing a bacterial cellulose / graphene nanosheet / carbon nanotube / polyethylene glycol blend from bacterial cellulose, a heat-conducting filler, a reducing agent and polyethylene glycol, and melting the bacterial cellulose / graphene nanosheet / carbon nanotube / polyethylene glycol blend, polylactic resin, a cross-linking agent, an antioxidant and a lubricant at 180-200 DEG C to obtain the composite material. The tensile strength of the composite material can be up to 55 MPa, the impact strength can be up to 10 kJ / m < 2 >, and the heat conductivity can be up to 7 w / m < 2 >. K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and particularly relates to a high-strength and high-toughness thermally conductive polylactic acid composite material and a preparation method thereof. The tensile strength of the composite material can be as high as 55MPa and the impact strength can be as high as 10kJ / m 2 , thermal conductivity can be as high as 7w / m 2 K: can be used in areas such as chip heat dissipation. Background Art

[0002] In recent years, with the depletion of oil resources and the increase of environmental awareness, the research and development of environmentally friendly bio-based polymer materials has received extensive attention from academia and industry. Polylactic acid, also known as polylactide, is a polymer obtained by polymerization of lactic acid as the main raw material. Due to its excellent biocompatibility and biodegradability, high mechanical strength and modulus, and easy processing and molding, it is one of the most actively studied bio-based polymer materials in recent years and has broad application prospects.

[0003] Due to the poor thermal conductivity and notched impact toughness of polylactic acid materials, their application areas are severely limited. Melting polylactic acid materials with elastomer materials and thermal conductive fillers is a common method to improve their notched impact toughness and thermal conductivity.

[0004] For example, the patent with application number CN201911027045.7 discloses a graphene thermal bridge material modified polylactic acid phase change energy storage material, which is prepared by uniformly mixing grafted graphene and polylactic acid, wherein the mass ratio of the grafted graphene to the polylactic acid is (8-2): (75-92); the mass ratio of the grafted graphene components is: 0.2-2 parts of graphite, 5-6 parts of maleic anhydride, and 20-30 parts of polyethylene glycol. With graphite, maleic anhydride, polyethylene glycol, and polylactic acid as raw materials, maleic anhydride and graphite undergo DielsAlder reaction to prepare functionalized graphene containing anhydride groups on the surface, which is then reacted with polyethylene glycol to obtain grafted modified graphene, which is used as a thermal bridge material in polylactic acid thermal conductive composite materials, effectively improving the thermal conductivity of polylactic acid composite materials and meeting the special requirements of the market for composite materials.

[0005] For example, the patent with application number CN201810562858.5 discloses a thermally conductive and electrically conductive polylactic acid 3D printing material, which is composed of the following components by mass: 30-90 parts of polylactic acid; 10-25 parts of graphene oxide; 0.5-3 parts of antioxidant; 3-7 parts of dispersant; 0.1-1 parts of nucleating agent; wherein the molecular weight of the polylactic acid is 40000-100000. The polylactic acid 3D printing material provided by the present invention has low density, thermal conductivity and electrical conductivity, which can meet the market demand for high thermal conductivity, electrical conductivity and low specific gravity FDM special consumables.

[0006] However, the introduction of elastomeric materials will inevitably reduce the strength of polylactic acid, and the thermal conductive filler is easy to agglomerate during the melt blending process. The improvement of thermal conductivity usually depends on a high content of thermal conductive filler. Under normal circumstances, the addition of thermal conductive filler will cause the mechanical properties of polylactic acid composites to decrease. It is difficult to achieve high tensile strength, impact strength and thermal conductivity with existing technologies. Summary of the invention

[0007] The purpose of the present invention is to provide a high-strength and high-toughness thermally conductive polylactic acid composite material, which uses polylactic acid as a resin matrix, bacterial cellulose and heterogeneous structure thermally conductive fillers work together, and uses water phase pre-dispersion and melt blending in-situ crosslinking technology as a method. Through the synergistic reinforcement and toughening of bacterial cellulose, graphene nanosheets and carbon nanotube nanofunctional fillers, combined with one-dimensional and two-dimensional heterogeneous structure thermally conductive fillers to construct a thermally conductive functional network, the polylactic acid composite material has both high thermal conductivity and high strength and high toughness, achieving multiple goals at one stroke. The technical solution provided by the present invention is: On the one hand, an embodiment of the present invention provides a high-strength and high-toughness thermally conductive polylactic acid composite material, which is made of the following raw materials in parts by weight: Polylactic acid resin 50-80 parts Bacterial cellulose 5-20 parts Thermal conductive filler 5-20 parts Polyethylene glycol 5-10 parts Reducing agent 1-5 parts Crosslinking agent 1-5 parts Antioxidant 0.2-2 parts Lubricant 0.2-2 parts.

[0008] The thermal conductive filler includes graphene oxide nanosheets and carboxylated carbon nanotubes, and the mass ratio of graphene oxide nanosheets to carboxylated carbon nanotubes is 1:0.1-10. The polylactic acid resin is selected from left-handed polylactic acid, right-handed polylactic acid or a mixture thereof. The molecular weight of polyethylene glycol is 1000-20000 g / mol. The reducing agent is selected from sodium citrate, tannic acid, vitamin C, glucose or amino acid; the cross-linking agent is selected from triallyl isocyanurate, hexamethylene diisocyanate trimer, n-butoxymethyl acrylamide or toluene diisocyanate trimer; the antioxidant and lubricant are common antioxidants and lubricants in polymer extrusion processing.

[0009] Among them, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend is prepared with bacterial cellulose, thermal conductive filler, reducing agent and polyethylene glycol, and bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, polylactic acid resin, crosslinking agent, antioxidant and lubricant are melted at 180-200°C to obtain a composite material.

[0010] In the bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, the role of bacterial cellulose in the bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend system is to act as a polymer carrier to ensure that the graphene nanosheets and carbon nanotubes are uniformly pre-dispersed. In the composite material obtained by subsequent melt blending of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol and polylactic acid, bacterial cellulose plays a role in strengthening and toughening. At the same time, bacterial cellulose acts as a three-dimensional material, two-dimensional graphene nanosheets and one-dimensional carbon nanotubes together; it also acts as a reinforcing component. The main function of the reducing agent is to reduce the graphene oxide nanosheets into graphene nanosheets with better electrical, thermal and mechanical properties. The reduction process allows the graphene nanosheets to be dispersed in the system. In this patent, the effect of directly using graphene nanosheets without reduction is not good. Polyethylene glycol is used as a polymer carrier to ensure that graphene nanosheets and carbon nanotubes are uniformly pre-dispersed, and to ensure that graphene nanosheets and carbon nanotubes can be uniformly dispersed in polylactic acid during melt blending with polylactic acid. Two-dimensional graphene nanosheets and one-dimensional carbon nanotubes constitute a heterogeneous structure. Preferably, the polylactic acid resin in the embodiment of the present invention is a stereocomplex polylactic acid with a right-handed polylactic acid content of 15-50 (specifically, mass content).

[0011] The graphene oxide nanosheets in the embodiment of the present invention have a sheet thickness of 1-10 nm and a sheet diameter greater than 10 μm. The carboxylated carbon nanotubes are selected from single-arm carbon nanotubes or multi-arm carbon nanotubes.

[0012] The antioxidant in the embodiment of the present invention includes a primary antioxidant and a secondary antioxidant, the primary antioxidant is antioxidant 1010, etc., the secondary antioxidant is antioxidant 168, etc., and the mass ratio of the primary antioxidant to the secondary antioxidant is 1:1.5-3.0. Preferably, the mass ratio of the primary antioxidant to the secondary antioxidant is 1:2.

[0013] Among them, the preparation method of the bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend in the embodiment of the present invention is: S101: dissolving bacterial cellulose in deionized water to obtain solution A, wherein the mass ratio of bacterial cellulose to deionized water is 1:6-12. S102: Add the thermal conductive filler into solution A according to the proportion, and perform ultrasonic treatment at a power of 100-800 W for 10-300 min to mix the thermal conductive filler and solution A to obtain solution B.

[0014] S103: Add a reducing agent to solution B according to the ratio, and react at 50-80° C. for 30-60 min to obtain solution C.

[0015] S104: Adding polyethylene glycol to solution C according to the ratio, stirring until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

[0016] Preferably, the high-strength and tough thermally conductive polylactic acid composite material in the embodiment of the present invention is made of the following raw materials in parts by weight: Polylactic acid resin 60-80 parts Bacterial cellulose 5-10 parts Thermal conductive filler 5-8 parts Polyethylene glycol 5-10 parts 2-3 parts reducing agent 2-4 parts of crosslinking agent Antioxidant 0.2-1 part Lubricant 0.2-1 part.

[0017] The thermal conductive filler comprises graphene oxide nanosheets and carboxylated carbon nanotubes, and the mass ratio of graphene oxide nanosheets to carboxylated carbon nanotubes is 1:0.4-3. The polylactic acid resin is a stereocomplex polylactic acid with a right-handed polylactic acid content of 15-50. The molecular weight of polyethylene glycol is 1000-20000g / mol. The sheet thickness of the graphene oxide nanosheet is 1-10nm, and the sheet diameter is greater than 10μm. The carboxylated carbon nanotubes are selected from single-arm carbon nanotubes or multi-arm carbon nanotubes. The reducing agent is selected from sodium citrate, tannic acid, vitamin C, glucose or amino acids. The cross-linking agent is selected from triallyl isocyanurate. The antioxidant comprises a primary antioxidant and an auxiliary antioxidant, the primary antioxidant is antioxidant 1010, the auxiliary antioxidant is antioxidant 168, and the mass ratio of the primary antioxidant to the auxiliary antioxidant is 1:1.5-3.0.

[0018] On the other hand, an embodiment of the present invention further provides a method for preparing the aforementioned high-strength and high-toughness thermally conductive polylactic acid composite material, the method comprising: (1) Bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blends were prepared using bacterial cellulose, thermal conductive filler, reducing agent and polyethylene glycol as raw materials.

[0019] (2) Polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, crosslinking agent, antioxidant and lubricant are mixed according to the proportion, and then melt-extruded at 180-200° C.

[0020] Wherein, the preparation method of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend is: S101: dissolving bacterial cellulose in deionized water to obtain solution A.

[0021] S102: Add the thermal conductive filler into solution A according to the proportion, and mix well to obtain solution B.

[0022] S103: Add a reducing agent to solution B according to the ratio, and react at 50-80° C. for 30-60 min to obtain solution C.

[0023] S104: Adding polyethylene glycol to solution C according to the ratio, stirring until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

[0024] Wherein, in step S101, the mass ratio of bacterial cellulose to deionized water is 1:6-12.

[0025] Preferably, in step S102, the thermal conductive filler and solution A are mixed by ultrasonic treatment at a power of 100-800 W for 10-300 min.

[0026] Specifically, in step (2), polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, crosslinking agent, antioxidant and lubricant are uniformly mixed by a high-speed mixer at a rotation speed of 500-1500 rpm; and extruded by a twin-screw extruder at a rotation speed of 200-300 rpm.

[0027] The present invention has the following advantages: (1) The present invention uses polylactic acid as the matrix and utilizes the structural and performance advantages of nanofillers such as one-dimensional carbon nanotubes, two-dimensional graphene nanosheets and three-dimensional bacterial cellulose, thereby achieving a synergistic improvement in thermal conductivity and mechanical properties and better balancing the processing performance of the material (there will be no agglomeration during the processing process).

[0028] (2) In the polymer blending and modification process in this patent, the dispersion and mixing of functional fillers is the key. The conventional melt blending process easily leads to the agglomeration of functional fillers and it is difficult to achieve the functional properties of the composite material. The present invention utilizes the excellent water dispersion properties of bacterial cellulose, polyethylene glycol, graphene oxide and carboxylated carbon nanotubes, and uses green solvent water as the dispersion medium to achieve uniform mixing of the reinforcing component bacterial cellulose, the toughening component polyethylene glycol and the thermal conductive filler graphene oxide and carboxylated carbon nanotubes, thereby obtaining a blend of bacterial cellulose / polyethylene glycol / graphene nanosheets / carbon nanotubes that can be uniformly dispersed during the melt blending process. The method provided by the present invention does not require special equipment and complex process flow, has controllable parameters, high preparation efficiency, and is suitable for large-scale preparation and application.

[0029] (3) The present invention makes full use of the interfacial compatibility between bacterial cellulose and graphene oxide nanosheets and carboxylated carbon nanotubes and the rich active groups such as hydroxyl and carboxyl groups on their surfaces. Through the reaction blending modification method, the dispersion state of bacterial cellulose, graphene oxide nanosheets and carboxylated carbon nanotubes in the polylactic acid matrix is ​​improved, and the synergistic enhancement, toughening and thermal conductivity of the polylactic acid composite material are greatly improved. Fusible polyethylene glycol is loaded on the surface of graphene nanosheets and carbon nanotubes, which can solve the dispersion problem of graphene nanosheets and carbon nanotubes on the one hand, and the cross-linking reaction with cross-linking agents such as triallyl isocyanurate during the blending process can also realize the toughness regulation of the polylactic acid material, which is beneficial to improve the toughness of the polylactic acid composite material.

[0030] (4) Using water as solvent reduces environmental pollution.

[0031] (5) The high-strength and tough thermally conductive polylactic acid composite material prepared by the present invention has good comprehensive performance, as shown in: the tensile strength can be as high as 55MPa and the impact strength can be as high as 10kJ / m 2 , thermal conductivity can be as high as 7w / m 2 ·K. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.

[0033] Example 1 Embodiment 1 provides a method for preparing a high-strength and high-toughness thermally conductive polylactic acid composite material, comprising the following steps: 1. Weigh 70 parts of polylactic acid resin, 6 parts of bacterial cellulose, 8 parts of thermal conductive filler, 8 parts of polyethylene glycol, 3 parts of vitamin C, 4 parts of triallyl isocyanurate, 0.5 parts of antioxidant and 0.5 parts of lubricant by weight. Among them, the thermal conductive filler includes graphene oxide nanosheets and carbon nanotubes, and the mass ratio of graphene oxide nanosheets to carboxylated carbon nanotubes is 1:0.4.

[0034] 2. Preparation of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blends: S201: According to the mass ratio of bacterial cellulose to deionized water being 1:9, the bacterial cellulose and deionized water are mixed and stirred uniformly to obtain solution A.

[0035] S202: Slowly adding a mixture of graphene oxide nanosheets and carboxylated carbon nanotubes in a mass ratio of 1:0.4 to solution A in batches according to the ratio, and then ultrasonically treating at a power of 500 W for 20 minutes to obtain solution B.

[0036] S203: Transfer solution B to a reactor at 80° C., add vitamin C according to the ratio and react for 45 minutes to obtain solution C.

[0037] S204: adding polyethylene glycol to solution C according to the ratio and stirring evenly until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

[0038] 3. A high-speed mixer is used to evenly mix polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, triallyl isocyanurate, an antioxidant and a lubricant according to a proportion at a rotation speed of 1000 rpm to obtain a mixed material; and then a twin-screw extruder is used to melt blend at 195°C and 300 r / min to obtain a high-strength, tough and thermally conductive polylactic acid composite material.

[0039] The experimental results show that the tensile strength of the polylactic acid composite material provided by the present invention is 68MPa and the impact strength is 15kJ / m 2 , thermal conductivity is 15w / m 2 ·K.

[0040] Example 2 Embodiment 2 provides a method for preparing a high-strength and high-toughness thermally conductive polylactic acid composite material, comprising the following steps: 1. Weigh 70 parts of polylactic acid resin, 8 parts of bacterial cellulose, 5 parts of thermal conductive filler, 10 parts of polyethylene glycol, 2 parts of glucose, 4 parts of toluene diisocyanate trimer, 0.5 parts of antioxidant and 0.5 parts of lubricant by weight. Among them, the thermal conductive filler includes graphene oxide nanosheets and carbon nanotubes, and the mass ratio of graphene oxide nanosheets to carboxylated carbon nanotubes is 1:0.4.

[0041] 2. Preparation of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blends: S201: According to the mass ratio of bacterial cellulose to deionized water being 1:9, the bacterial cellulose and deionized water are mixed and stirred uniformly to obtain solution A.

[0042] S202: Slowly adding a mixture of graphene oxide nanosheets and carboxylated carbon nanotubes in a mass ratio of 1:0.4 to solution A in batches according to the ratio, and then ultrasonically treating the solution at a power of 400 W for 25 minutes to obtain solution B.

[0043] S203: Transfer solution B to a reactor at 80° C., add glucose according to the ratio and react for 45 minutes to obtain solution C.

[0044] S204: adding polyethylene glycol to solution C according to the ratio and stirring evenly until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheet / carbon nanotube / polyethylene glycol blend; 3. A high-speed mixer is used to evenly mix polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, toluene diisocyanate trimer, antioxidant and lubricant at a rotation speed of 1000 rpm to obtain a mixed material; a twin-screw extruder is then used to melt-blend at 200°C and 270 r / min to obtain a high-strength, tough and thermally conductive polylactic acid composite material.

[0045] The experimental results show that the tensile strength of the polylactic acid composite material provided by the present invention is 62MPa and the impact strength is 21kJ / m 2 , thermal conductivity is 10w / m 2 ·K.

[0046] Example 3 Example 3 provides a method for preparing a high-strength and high-toughness thermally conductive polylactic acid composite material, comprising the following steps: 1. Weigh 80 parts of polylactic acid resin, 5 parts of bacterial cellulose, 5 parts of thermal conductive filler, 5 parts of polyethylene glycol, 2 parts of sodium citrate, 2 parts of hexamethylene diisocyanate trimer, 0.5 parts of antioxidant and 0.5 parts of lubricant by weight. Among them, the thermal conductive filler includes graphene oxide nanosheets and carbon nanotubes, and the mass ratio of graphene oxide nanosheets to carboxylated carbon nanotubes is 1:0.4.

[0047] 2. Preparation of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blends: S201: According to the mass ratio of bacterial cellulose to deionized water being 1:9, the bacterial cellulose and deionized water are mixed and stirred uniformly to obtain solution A.

[0048] S202: Slowly adding a mixture of graphene oxide nanosheets and carboxylated carbon nanotubes in a mass ratio of 1:0.4 to solution A in batches according to the ratio, and then ultrasonically treating at a power of 500 W for 20 minutes to obtain solution B.

[0049] S203: Transfer solution B to a reactor at 60° C., add sodium citrate according to the ratio and react for 60 minutes to obtain solution C.

[0050] S204: adding polyethylene glycol to solution C according to the ratio and stirring evenly until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

[0051] 3. A high-speed mixer is used to evenly mix polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, hexamethylene diisocyanate trimer, antioxidant and lubricant at a rotation speed of 1000 rpm to obtain a mixed material; and then a twin-screw extruder is used to melt-blend at 198°C and 275r / min to obtain a high-strength, tough and thermally conductive polylactic acid composite material.

[0052] The experimental results show that the tensile strength of the polylactic acid composite material provided by the present invention is 74MPa and the impact strength is 10kJ / m 2 , thermal conductivity is 7.6w / m 2 ·K.

[0053] Example 4 Example 4 provides a method for preparing a high-strength and high-toughness thermally conductive polylactic acid composite material, comprising the following steps: 1. Weigh 60 parts of polylactic acid resin, 10 parts of bacterial cellulose, 8 parts of thermal conductive filler, 10 parts of polyethylene glycol, 2 parts of glucose, 4 parts of triallyl isocyanurate, 0.5 parts of antioxidant and 0.5 parts of lubricant by weight. Among them, the thermal conductive filler includes graphene oxide nanosheets and carbon nanotubes, and the mass ratio of graphene oxide nanosheets to carboxylated carbon nanotubes is 1:0.4.

[0054] 2. Preparation of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blends: S201: According to the mass ratio of bacterial cellulose to deionized water being 1:8, the bacterial cellulose and deionized water are mixed and stirred uniformly to obtain solution A.

[0055] S202: Slowly adding a mixture of graphene oxide nanosheets and carboxylated carbon nanotubes in a mass ratio of 1:0.4 to solution A in batches according to the ratio, and then ultrasonically treating at a power of 600 W for 20 minutes to obtain solution B.

[0056] S203: Transfer solution B to a reactor at 80° C., add glucose according to the ratio and react for 40 minutes to obtain solution C.

[0057] S204: adding polyethylene glycol to solution C according to the ratio and stirring evenly until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

[0058] 3. A high-speed mixer is used to evenly mix polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, triallyl isocyanurate, an antioxidant and a lubricant according to a proportion at a rotation speed of 1000 rpm to obtain a mixed material; and then a twin-screw extruder is used to melt-blend at 200°C and 300 r / min to obtain a high-strength, tough and thermally conductive polylactic acid composite material.

[0059] The experimental results show that the tensile strength of the polylactic acid composite material provided by the present invention is 58MPa and the impact strength is 26kJ / m 2 , thermal conductivity is 14w / m 2 ·K.

[0060] Example 5 Example 5 provides a method for preparing a high-strength and high-toughness thermally conductive polylactic acid composite material, comprising the following steps: 1. Weigh 70 parts of polylactic acid resin, 6 parts of bacterial cellulose, 8 parts of thermal conductive filler, 8 parts of polyethylene glycol, 3 parts of tannic acid, 4 parts of triallyl isocyanurate, 0.5 parts of antioxidant and 0.5 parts of lubricant by weight. Among them, the thermal conductive filler includes graphene oxide nanosheets and carbon nanotubes, and the mass ratio of graphene oxide nanosheets to carboxylated carbon nanotubes is 1:3.

[0061] 2. Preparation of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blends: S201: According to the mass ratio of bacterial cellulose to deionized water being 1:11, the bacterial cellulose and deionized water are mixed and stirred uniformly to obtain a solution A.

[0062] S202: Slowly adding a mixture of graphene oxide nanosheets and carboxylated carbon nanotubes in a mass ratio of 1:3 to solution A in batches according to the ratio, and then ultrasonically treating the solution at a power of 750 W for 20 minutes to obtain solution B.

[0063] S203: Transfer solution B to a reactor at 75° C., add tannic acid according to the ratio and react for 45 minutes to obtain solution C.

[0064] S204: adding polyethylene glycol to solution C according to the ratio and stirring evenly until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

[0065] 3. A high-speed mixer is used to evenly mix polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, triallyl isocyanurate, an antioxidant and a lubricant at a rotation speed of 1000 rpm to obtain a mixed material; and then a twin-screw extruder is used to melt-blend at 188°C and 280 r / min to obtain a high-strength, tough and thermally conductive polylactic acid composite material.

[0066] The experimental results show that the tensile strength of the polylactic acid composite material provided by the present invention is 64MPa and the impact strength is 13kJ / m 2 , thermal conductivity is 12w / m 2 ·K.

[0067] Comparative Example 1 Comparative Example 1 is substantially the same as Example 1, except that bacterial cellulose, graphene oxide nanosheets, carboxylated carbon nanotubes, vitamin C and polyethylene glycol are not blended but are directly mixed with polylactic acid resin, triallyl isocyanurate, antioxidant and lubricant.

[0068] The experimental results show that the tensile strength of the polylactic acid composite material provided in this comparative example can reach 48MPa and the impact strength can reach 4kJ / m 2 , thermal conductivity can reach 3w / m 2 · K. The tensile strength, impact strength and thermal conductivity are all low.

[0069] Comparative Example 2 Comparative Example 2 is substantially the same as Example 1, except that bacterial cellulose is not added in step 2, but is added in step 3.

[0070] The experimental results show that the tensile strength of the polylactic acid composite material obtained in this comparative example is 52MPa and the impact strength is 8kJ / m 2 , thermal conductivity is 7w / m 2 · K. Low tensile strength and impact strength.

[0071] Comparative Example 3 Comparative Example 3 is substantially the same as Example 1, except that bacterial cellulose is not added in step 2.

[0072] The experimental results show that the tensile strength of the polylactic acid composite material obtained in this comparative example is 45MPa and the impact strength is 8kJ / m 2 , thermal conductivity is 10w / m 2 · K. The tensile strength is low, and combined with Comparative Example 2, it can be seen that the addition of bacterial cellulose (in another step) will reduce the tensile strength and thermal conductivity.

[0073] Comparative Example 4 Comparative Example 4 is substantially the same as Example 1, except that polyethylene glycol is not added in step 2.

[0074] The experimental results show that the tensile strength of the polylactic acid composite material obtained in this comparative example is 49MPa and the impact strength is 5kJ / m 2 , thermal conductivity is 10w / m 2· K. Low tensile strength and impact strength.

[0075] Comparative Example 5 Comparative Example 5 is substantially the same as Example 1, except that graphene nanosheets are added in step 2, and step S203 is not performed.

[0076] The experimental results show that the tensile strength of the polylactic acid composite material obtained in this comparative example is 51MPa and the impact strength is 6kJ / m 2 , thermal conductivity is 7w / m 2 K. If the graphene nanosheets do not undergo reduction reaction, the overall performance will decrease.

[0077] Comparative Example 6 Comparative Example 6 is substantially the same as Example 1, except that in step S202, ultrasonic treatment is not performed and direct mixing is adopted.

[0078] The experimental results show that the tensile strength of the polylactic acid composite material obtained in this comparative example is 62MPa and the impact strength is 13kJ / m 2 , thermal conductivity is 11w / m 2 · K. Without ultrasonic treatment, the tensile strength, impact strength and thermal conductivity all decreased slightly, with the thermal conductivity decreasing most significantly.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. High-strength and high-toughness thermally conductive polylactic acid composite material, characterized in that: Made from the following raw materials in parts by weight: Polylactic acid resin 50-80 parts Bacterial cellulose 5-20 parts Thermal conductive filler 5-20 parts Polyethylene glycol 5-10 parts Reducing agent 1-5 parts Crosslinking agent 1-5 parts Antioxidant 0.2-2 parts Lubricant 0.2-2 parts; The thermal conductive filler comprises graphene oxide nanosheets and carboxylated carbon nanotubes, wherein the mass ratio of the graphene oxide nanosheets to the carboxylated carbon nanotubes is 1:0.1-10; the polylactic acid resin is selected from left-handed polylactic acid or right-handed polylactic acid; the molecular weight of the polyethylene glycol is 1000-20000 g / mol; the reducing agent is selected from sodium citrate, tannic acid, vitamin C, glucose or amino acid; the cross-linking agent is selected from triallyl isocyanurate, hexamethylene diisocyanate trimer, n-butoxymethyl acrylamide or toluene diisocyanate trimer; The bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend is prepared with bacterial cellulose, a thermal conductive filler, a reducing agent and polyethylene glycol, and the bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, polylactic acid resin, a crosslinking agent, an antioxidant and a lubricant are melted at 180-200° C. to obtain a composite material.

2. The high-strength and thermally conductive polylactic acid composite material according to claim 1, characterized in that: The polylactic acid resin is a stereocomplex polylactic acid with a dextrorotatory polylactic acid content of 15-50.

3. The high-strength and tough thermally conductive polylactic acid composite material according to claim 1, characterized in that: The graphene oxide nanosheet has a sheet thickness of 1-10 nm and a sheet diameter greater than 10 μm; the carboxylated carbon nanotube is selected from a single-arm carbon nanotube or a multi-arm carbon nanotube.

4. The high-strength and thermally conductive polylactic acid composite material according to claim 1, characterized in that: The antioxidant comprises a primary antioxidant and a secondary antioxidant, the primary antioxidant is antioxidant 1010, the secondary antioxidant is antioxidant 168, and the mass ratio of the primary antioxidant to the secondary antioxidant is 1:1.5-3.

0.

5. The high-strength and thermally conductive polylactic acid composite material according to claim 1, characterized in that: The preparation method of the bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend is as follows: S101: dissolving bacterial cellulose in deionized water to obtain solution A; S102: adding the thermal conductive filler into solution A according to the proportion, and mixing to obtain solution B; S103: Add a reducing agent to solution B according to the ratio, and react at 50-80° C. for 30-60 min to obtain solution C; S104: Adding polyethylene glycol to solution C according to the ratio, stirring until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

6. The high-strength and tough thermally conductive polylactic acid composite material according to claim 1, characterized in that: Made from the following raw materials in parts by weight: Polylactic acid resin 60-80 parts Bacterial cellulose 5-10 parts Thermal conductive filler 5-8 parts Polyethylene glycol 5-10 parts 2-3 parts reducing agent 2-4 parts of crosslinking agent Antioxidant 0.2-1 part Lubricant 0.2-1 part; Among them, the thermal conductive filler includes graphene oxide nanosheets and carboxylated carbon nanotubes, and the mass ratio of the graphene oxide nanosheets to the carboxylated carbon nanotubes is 1:0.4-3; the polylactic acid resin is a stereocomplex polylactic acid with a right-handed polylactic acid content of 15-50; the molecular weight of the polyethylene glycol is 1000-20000g / mol; the sheet thickness of the graphene oxide nanosheets is 1-10nm, and the sheet diameter is greater than 10μm; the carboxylated carbon nanotubes are selected from single-arm carbon nanotubes or multi-arm carbon nanotubes; the reducing agent is selected from sodium citrate, tannic acid, vitamin C, glucose or amino acids; the cross-linking agent is selected from triallyl isocyanurate; the antioxidant includes a main antioxidant and a secondary antioxidant, the main antioxidant is antioxidant 1010, the secondary antioxidant is antioxidant 168, and the mass ratio of the main antioxidant to the secondary antioxidant is 1:1.5-3.

0.

7. The method for preparing the high-strength and tough thermally conductive polylactic acid composite material according to any one of claims 1 to 6, characterized in that: The method comprises: (1) preparing bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blends using bacterial cellulose, thermal conductive filler, reducing agent and polyethylene glycol as raw materials; (2) mixing polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, a crosslinking agent, an antioxidant and a lubricant according to a proportion, and then melt-extruding at 180-200° C.; Wherein, the preparation method of bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend is: S101: dissolving bacterial cellulose in deionized water to obtain solution A; S102: adding the thermal conductive filler into solution A according to the proportion, and mixing to obtain solution B; S103: Add a reducing agent to solution B according to the ratio, and react at 50-80° C. for 30-60 min to obtain solution C; S104: Adding polyethylene glycol to solution C according to the ratio, stirring until the polyethylene glycol is completely dissolved, and then performing supercritical drying to obtain a bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend.

8. The preparation method according to claim 7, characterized in that: In step S101, the mass ratio of bacterial cellulose to deionized water is 1:6-12.

9. The preparation method according to claim 7, characterized in that: In step S102, the thermal conductive filler and solution A are mixed by ultrasonic treatment at a power of 100-800 W for 10-300 min.

10. The preparation method according to claim 7, characterized in that: In step (2), polylactic acid resin, bacterial cellulose / graphene nanosheets / carbon nanotubes / polyethylene glycol blend, crosslinking agent, antioxidant and lubricant are uniformly mixed by a high-speed mixer at a rotation speed of 500-1500 rpm; and extruded by a twin-screw extruder at a rotation speed of 200-300 rpm.

Citation Information

Patent Citations

  • Thermal and electric conducting polyactic acid 3D printing material and preparation method and application thereof

    CN108841146A

  • Graphene thermal bridge material modified polylactic acid phase-change energy storage material and preparation method thereof

    CN111534063A

  • Polylactic acid / polyethylene glycol / carbon nano tube composite material and preparation method thereof

    CN103665799A

  • Preparation method of high-conductive-stability graphene composite material

    CN104629275A

  • Cellulose nano fiber / polylactic acid composite material and preparation method thereof

    CN105885367A